1992
DOI: 10.1111/j.1365-2141.1992.tb02993.x
|View full text |Cite
|
Sign up to set email alerts
|

Lupus‐like anticoagulant properties of murine monoclonal antibodies to β2‐glycoprotein I

Abstract: The lipid-binding inhibitor of coagulation, beta 2-glycoprotein I (beta 2GPI), has been shown to form the antigen to which some autoantibodies against anionic phospholipids (aPL) are directed. Six murine monoclonal antibodies (MAbs) of the IgG1 isotype were raised against human beta 2GPI and could be subdivided into three groups on the basis of mutual competition experiments. MAbs 9G1 and 8C3 (group A) markedly inhibited the binding of immunoglobulins from aPL-positive sera to beta 2GPI-coated wells. Using a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 26 publications
7
36
0
Order By: Relevance
“…The importance of immunoglobulin receptors as potential initiators of thrombosis is supported by 1) emerging evidence that aCL binding to platelets and neutrophils leads to activation via cellular FcyR (33,34), 2) the precedent of an FcyR-dependent mechanism of thrombosis in heparin-induccd thrombocytopenia (35), and 3) the case reports of successful treatment of APS with high-dose intravenous gamma globulin (36,37). The presence of IgG2 aCL in association with FcyRIIA-H131 may therefore be a useful clinical predictor of increased thrombotic risk in patients with autoimmune IgG aCL.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of immunoglobulin receptors as potential initiators of thrombosis is supported by 1) emerging evidence that aCL binding to platelets and neutrophils leads to activation via cellular FcyR (33,34), 2) the precedent of an FcyR-dependent mechanism of thrombosis in heparin-induccd thrombocytopenia (35), and 3) the case reports of successful treatment of APS with high-dose intravenous gamma globulin (36,37). The presence of IgG2 aCL in association with FcyRIIA-H131 may therefore be a useful clinical predictor of increased thrombotic risk in patients with autoimmune IgG aCL.…”
Section: Discussionmentioning
confidence: 99%
“…Two anti-b2-gpI mAbs were supplied by Josiane Arvieux (Brest, France): the 9G1 mAb that recognizes both human and bovine b2-gpI, and the 8C3 mAb that is specific for human b2-gpI (35). The 6C4 mAb (36) directed to Lactoferin-binding protein A and specific for late endosomes was donated by Jean Gruenberg (Geneva, Switzerland).…”
Section: Monoclonal and Polyclonal Absmentioning
confidence: 99%
“…An ELISA was developed to quantitate specifically human b2-gpI (35). It combined the capture human-specific anti-b2-gpI 8C3 mAb, a rabbit anti-b2-gpI Ab, and the developing HRP-goat anti-rabbit Ig Ab (Jackson ImmunoResearch Laboratories).…”
Section: Preparation Of B2-gpimentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies showed that the binding of ACA to cardiolipin (CL) was markedly enhanced by a plasma protein, (32 glycoprotein 1 (f32GP1), suggesting that ACA reacted with phospholipidf32GP1 complexes- (11)(12)(13)(14)(15). In contrast, other laboratories reported that these antibodies bound f32GP1 alone (16)(17)(18)(19)(20)(21)(22). However, some laboratories failed to detect similar direct anti-(32GP1 binding (15,23).…”
mentioning
confidence: 99%